Oxygen saturation measurement in cyanotic heart disease with the Apple watch - Weis, Angelika; Leroy, Martin; Jux, Christian; Rupp, Stefan; Backhoff, David; Justus Liebig University Giessen (My University, 2024)
Background: Accurate measurement of transcutaneous oxygen saturation is important for the assessment of cyanosis in CHD. Aim of this study was the evaluation of a supplementary transcutaneous oxygen saturation measurement with an Apple watch® in children with cyanotic heart disease. Material and methods: During a six-minute walk test, measurement of transcutaneous oxygen saturation was performed simultaneously with an Oximeter (Nellcor, Medtronic, USA) and an Apple watch® Series 7 (Apple inc, USA) in 36 children with cyanotic heart disease. Results: Median age was 9.2 (IQR 5.7–13.8) years. Transcutaneous oxygen saturation measurement with the Apple watch® was possible in 35/36 and 34/36 subjects before and after six-minute walk test. Children, in whom Apple watch® measurement was not possible, had a transcutaneous oxygen saturation < 85% on oximeter. Before six-minute walk test, median transcutaneous oxygen saturation was 93 (IQR 91–97) % measured by oximeter and 95 (IQR 93–96) % by the Apple watch®. After a median walking distance of 437 (IQR 360–487) m, transcutaneous oxygen saturation dropped to 92 (IQR 88–95, p < 0.001) % by oximeter and to 94 (IQR 90–96, p = 0.013) % measured with the Apple watch®. Conclusion: In children with mild cyanosis measurement of transcutaneous oxygen saturation with an Apple watch® showed only valid results if transcutaneous oxygen saturation was > 85%, with higher values being measured with the smart watch. In children with moderate or severe cyanosis transcutaneous oxygen saturation, measurement with the Apple watch® was not reliable and cannot be recommended to monitor oxygen saturation at home.
Keywords: ddc:610